Anomalous Light‐Induced Spin‐State Switching for Iron(II) Spin‐Crossover Molecules in Direct Contact with Metal Surfaces. (3rd June 2020) - Zhang, Luqiong; Tong, Yongfeng; Kelai, Massine; Bellec, Amandine; Lagoute, Jérôme; Chacon, Cyril; Girard, Yann; Rousset, Sylvie; Boillot, Marie‐Laure; Rivière, Eric; Mallah, Talal; Otero, Edwige; et al.
Abstract: Light‐induced spin‐state switching is one of the most attractive properties of spin‐crossover materials. In bulk, low‐spin (LS) to high‐spin (HS) conversion via the light‐induced excited spin‐state trapping (LIESST) effect may be achieved with a visible light, while the HS‐to‐LS one (reverse‐LIESST) requires an excitation in the near‐infrared range. Now, it is shown that those phenomena are strongly modified at the interface with a metal. Indeed, an anomalous spin conversion is presented from HS state to LS state under blue light illumination for Fe II spin‐crossover molecules that are in direct contact with metallic (111) single‐crystal surfaces (copper, silver, and gold). To interpret this anomalous spin‐state switching, a new mechanism is proposed for the spin conversion based on the light absorption by the substrate that can generate low energy valence photoelectrons promoting molecular vibrational excitations and subsequent spin‐state switching at the molecule–metal interface. Abstract : Substrate‐induced switching : A Fe II spin‐crossover molecule at the interface with metals switches from a high‐spin to low‐spin state with visible light. This result is the complete opposite of what is known for the bulk materials. Therefore, for spin‐crossover compounds, the interface matters.